Modeling the effect of agricultural best management practices on water quality under various climatic scenarios. Issue 1 (11th December 2007) - Parker, G. T.; Droste, R. L.; Kennedy, K. J.
Abstract : The South Nation (SN) watershed in Eastern Ontario was studied for improvements in surface water quality due to best management practices (BMPs). Contributions of non-point sources (NPS) to nutrient loadings are both significant and poorly defined in the region. The study used the dynamic Annualized Agricultural NPS (AnnAGNPS) model to run continuous annual simulations, coupled with a dynamic water-quality model for simulation of riverine water chemistry. The simulation case matrix focused on the potential of BMPs within the context of climate change. Results of the work were then analyzed to determine ecological intensity (severity), duration, and frequency (IDF) of violations to species survivability within the stream network. Best management practices were found to reduce water quality impacts but stream standards were not reached. Adjustment of fertilizer application rates (FAR) and vegetative filter strips (VFS) outperformed alternative BMPs in the model. Results suggest that agricultural activity within the watershed must be diminished to reach standards.